2018
DOI: 10.1111/cge.13200
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic exome sequencing in children: A survey of parental understanding, experience and psychological impact

Abstract: Clinical exome sequencing (CES) is increasingly being used as an effective diagnostic tool in the field of pediatric genetics. We sought to evaluate the parental experience, understanding and psychological impact of CES by conducting a survey study of English-speaking parents of children who had diagnostic CES. Parents of 192 unique patients participated. The parent's interpretation of the child's result agreed with the clinician's interpretation in 79% of cases, with more frequent discordance when the clinici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
42
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 38 publications
3
42
0
Order By: Relevance
“…Parents in that study commented in particular on their concern regarding the turnaround time of ES. The average patient age in this study was 6.8 years (Wynn et al, 2018). Anecdotally, this concern was voiced by some parents in the NICU cohort during pre-test genetic counseling.…”
Section: Causes % Of Participants Significancementioning
confidence: 88%
“…Parents in that study commented in particular on their concern regarding the turnaround time of ES. The average patient age in this study was 6.8 years (Wynn et al, 2018). Anecdotally, this concern was voiced by some parents in the NICU cohort during pre-test genetic counseling.…”
Section: Causes % Of Participants Significancementioning
confidence: 88%
“…In SCN1A -related epilepsy, duration of use of contraindicated sodium-channel blocking medication is associated with adverse developmental outcome ( de Lange et al , 2018 ). Additional benefits of early genetic diagnosis in epilepsy include providing information for genetic counselling ( Krabbenborg et al , 2016 ), giving answers for affected families ( Brunklaus et al , 2013 ; Sawyer et al , 2016 ; Wynn et al , 2018 ), and avoidance of additional costly and invasive investigations. Recent economic analyses have demonstrated that the application of early high throughput genetic testing could save $5236 Australian dollars ( Palmer et al , 2018 ), or $7047 US dollars ( Howell et al , 2018 ) per diagnosis when compared with investigation programs that involved extensive imaging and metabolic testing prior to genetic testing.…”
Section: Discussionmentioning
confidence: 99%
“…A study of parents whose children had diagnostic ES (n=192) demonstrated that parents of tested children experienced psychological responses to testing including worry, fear and relief with test related distress and uncertainty higher among those whose children received a genetic diagnosis. 12 A longitudinal cohort study of individuals undergoing GS (n=35) noted that test distress was low and that most participants were happy or relieved about their results. 13 In order to more completely explore the effects of the clinical integration of ES/GS across multiple clinical contexts and patient populations, the National Human Genome Research Institute launched the Clinical Sequencing Exploratory Research (phase1; CSER1) Consortium.…”
Section: Introductionmentioning
confidence: 99%